Attitudes and perceptions of the general public on obesity and its treatment options in Singapore. Issue 4 (July 2019) - Lee, Phong Ching; Ganguly, Sonali; Tan, Hong Chang; Lim, Chin Hong; Chan, Weng Hoong; Kovalik, Jean-Paul; Eng, Alvin; Tan, Jeremy; Lim, Eugene; Chua, Jasmine; Tham, Kwang Wei
Abstract: Data on attitudes and perceptions towards obesity are lacking in Asia. Participants who attended an obesity public forum were surveyed concerning obesity and its treatment options. Although obesity is generally accepted as a disease with biological underpinnings such as hormonal imbalances and slow metabolic rate, it is also regarded as an issue of personal responsibility. 65.1% believed that weight-loss medications are dangerous. 20.6% thought that pharmacotherapy is effective for weight loss, whereas 41.1% were unsure. Most believed that bariatric surgery could improve health (81.9%) and diabetes control (74.0%) although 64.1% were unsure of its risks.